2014
DOI: 10.1111/jsr.12148
|View full text |Cite
|
Sign up to set email alerts
|

Sleep continuity and total sleep time are associated with task‐switching and preparation in young and older adults

Abstract: Summary Aging is associated with changes in sleep and decline executive functions, such as task-switching and task preparation. Given that sleep affects executive function, age-related changes in executive function may be attributable to changes in sleep. The present study used a sleep detection device to examine whether wake time after sleep onset (WASO) and total sleep time (TST) moderated age differences in task-switching performance and participants' ability to reduce switch costs when given time to prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 33 publications
(44 reference statements)
6
33
0
Order By: Relevance
“…We did not find any significant associations between total sleep duration and cognitive performance at any of the three measured time periods. These results are consistent with previous studies (Blackwell et al, 2006; Wilckens, Woo, Erickson, & Wheeler, 2014), which demonstrated that sleep continuity was more important to cognitive functioning than total sleep time for older adults. In the present study, disturbed sleep lost its significant association with working memory when we examined only the one night’s sleep prior to testing, suggesting that only one night of mildly disturbed sleep has less of an impact on cognitive performance than chronic mildly disturbed sleep in healthy, cognitively intact older adults.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find any significant associations between total sleep duration and cognitive performance at any of the three measured time periods. These results are consistent with previous studies (Blackwell et al, 2006; Wilckens, Woo, Erickson, & Wheeler, 2014), which demonstrated that sleep continuity was more important to cognitive functioning than total sleep time for older adults. In the present study, disturbed sleep lost its significant association with working memory when we examined only the one night’s sleep prior to testing, suggesting that only one night of mildly disturbed sleep has less of an impact on cognitive performance than chronic mildly disturbed sleep in healthy, cognitively intact older adults.…”
Section: Methodssupporting
confidence: 93%
“…These results suggest that in community dwelling cognitively intact older adults who generally sleep well (about 8 hours per night), small reductions in sleep duration and sleep quality might be less directly related to cognitive performance than other lifestyle factors such as pain, low mood, overall health, and medications that can impact cognition. The most consistent findings in the literature regarding the impact of sleep on cognition in older adults have been shown in the areas of attention, working memory, and executive functioning (Blackwell et al, 2011a; Wilckens et al, 2014). However, methodological differences between these previous studies and the current study could explain why we did not find stronger associations between sleep and cognition in the current study.…”
Section: Methodsmentioning
confidence: 66%
“…Much of the literature to date has focused on the role of sleep in memory consolidation in older adults (Mander et al, 2013; Pace-Schott & Spencer, 2011; Spencer, Gouw, & Ivry, 2007; Tucker, McKinley, & Stickgold, 2011; Wilson, Baran, Pace-Schott, Ivry, & Spencer, 2012). However, other aspects of cognition, including controlled memory processes and executive functions, show dramatic decline into older adulthood (Braver & West, 2008; Buckner, 2004; Verhaeghen & Cerella, 2002), and age-related changes in sleep may affect these domains of cognition (Anderson & Horne, 2003; Pace-Schott & Spencer, 2011; Terry, Anderson, & Horne, 2004; Wilckens et al, 2012; Wilckens, Woo, Erickson, & Wheeler, 2014). Notably, it remains an open question as to whether improving age-related sleep changes may lead to improvements in executive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep continuity, total sleep time (TST), slow-wave sleep, sleep spindles, and rapid eye movement (REM) sleep have all been associated with some aspects of cognition. Sleep continuity is a particularly interesting sleep variable from the perspective of cognitive aging, given that sleep continuity decreases in older adulthood, and habitual and experimentally manipulated sleep continuity are associated with executive function (Blackwell et al, 2006; Martin, Engleman, Deary, & Douglas, 1996; Nebes, Buysse, Halligan, Houck, & Monk, 2009; Verstraeten & Cluydts, 2004; Wilckens, Woo, Erickson, et al, 2014; Wilckens, Woo, Kirk, Erickson, & Wheeler, 2014). Insomnia, which is often associated with poor sleep continuity, has been associated with poorer executive abilities relative to good-sleeping controls (Altena, Van Der Werf, Strijers, & Van Someren, 2008; Caplette-Gingras, Savard, Savard, & Ivers, 2013; Fortier-Brochu, Beaulieu-Bonneau, Ivers, & Morin, 2012; Fulda & Schulz, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation